2006
DOI: 10.2174/138955706778195207
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Proteinase Inhibitors as Therapy for Parasitic Diseases: Advances in Inhibitor Design

Abstract: Clan CA (papain-like) cysteine proteinases of protozoan parasites are validated targets for the rational design of new anti-parasitic chemotherapies. Peptidyl and peptidomimetic proteinase inhibitors of differing chemistries limit parasite survival in vitro and in vivo. Also, the development of activity-based affinity labels has enabled the identification and characterization of potential cysteine proteinase targets in situ. This article reviews the biology and physicochemistry of parasite proteinases and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
(140 reference statements)
0
15
0
Order By: Relevance
“…The inhibitors include the following: (i) epoxide inhibitor CA074, a specific inhibitor of cathepsin B-type peptidases (17) that has been previously structurally characterized in complex with mammalian cathepsins B (18), and (ii) vinyl sulfone inhibitors K11017 and K11777 that have not been crystallographically studied so far in complex with cathepsins B. Vinyl sulfones are effective against papain-like cysteine peptidases and were originally investigated in the context of inhibiting human cathepsins (19,20). Later, they were demonstrated to inhibit cysteine peptidases from a variety of protozoan pathogens such as Trypanosoma and Plasmodium, and provide either parasitological cure or a temporary remission of parasitemia (21)(22)(23). As a chemotype, vinyl sulfones have acceptable pharmacokinetic attributes and in vivo safety profiles (24,25).…”
Section: Schistosomiasis Caused By a Parasitic Blood Fluke Of The Genusmentioning
confidence: 99%
“…The inhibitors include the following: (i) epoxide inhibitor CA074, a specific inhibitor of cathepsin B-type peptidases (17) that has been previously structurally characterized in complex with mammalian cathepsins B (18), and (ii) vinyl sulfone inhibitors K11017 and K11777 that have not been crystallographically studied so far in complex with cathepsins B. Vinyl sulfones are effective against papain-like cysteine peptidases and were originally investigated in the context of inhibiting human cathepsins (19,20). Later, they were demonstrated to inhibit cysteine peptidases from a variety of protozoan pathogens such as Trypanosoma and Plasmodium, and provide either parasitological cure or a temporary remission of parasitemia (21)(22)(23). As a chemotype, vinyl sulfones have acceptable pharmacokinetic attributes and in vivo safety profiles (24,25).…”
Section: Schistosomiasis Caused By a Parasitic Blood Fluke Of The Genusmentioning
confidence: 99%
“…[5] A number of reports in recent years have described the inhibitory activity of several families of compounds such as Nacylhydrazides, chalcones, ureas, thioureas, and thiosemicarbazones toward TCC, and the relationship with their in vitro trypanocidal activity (Figure 1). [6][7][8] For example, Greenbaum et al described 3'-bromopropiophenone and 3-trifluormethylphenyl thiosemicarbazone as the most effective cruzain inhibitors, with trypanocidal activity at levels that are nontoxic to mammalian cells. [9] To compare these findings, Fujii et al [10] investigated thiosemicarbazones that possess larger alkyl groups at the adjoining hydrazone and reported that they are most active with an n-butyl group linked to the 3,4-dichlorobenzoyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in intracellular replication and differentiation, and is essential at all stages of the parasite's life cycle. Inhibitors of cruzain [3][4][5][6] display considerable antitrypanosomal activity 7,8 and some classes have been shown to cure T. cruzi infection in mouse models [7][8][9][10] . Since currently available therapeutics is practically ineffective in the acute phase of the disease besides being highly toxic to be safely administered for long periods, efforts have been made with a view to characterizing new therapeutic targets, among which the proteolytic apparatus of T. cruzi is a possible candidate 11 .…”
Section: Introductionmentioning
confidence: 99%